Conducting rigorous avian inventories: Amazonian case studies and a roadmap for improvement - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2014)
Site-based avian inventories are ubiquitous in Neotropical ornithology but are prone to error if fieldworkers are not familiar with the regional species pool, particularly in species-rich regions such as the Amazon basin. Here, we review recent species lists from the Brazilian Amazon in both the primary ornithological literature and in protected area management plans to assess the level of putative errors in terms of bird species recorded in site-based inventories that are biogeographically unlikely in the sampled region. We found errors to be frequent across all inventory types. Failure to recognize recent taxonomic modifications in a cited taxonomy was a common error in many inventories. We outline a series of steps to follow to improve the utility and accuracy of avian inventories, and stress the importance of both obtaining and archiving documentary material, which should be included in the publications as digital vouchers to facilitate detailed peer review.
Condução de inventários aviários rigorosos: estudos de casos da Amazônia e um roteiro para melhoria
Keywords: Amazonia; avian surveys; checklist; documentation; taxonomy; vouchers; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA